THE LAW OF RECEIVING WAGES FOR TEACHERS OF THE QURAN, THE PERSPECTIVE OF ULAMA SYAFIIYAH AND HANAFIYYAH - Rizky Rizky; Mohamad Hidayatullah AK Husein; Nenden Herawaty Suleman (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
The Syafiiyah and Hanafiyah scholars' perspectives on the background of their divergent viewpoints on the legality of receiving compensation for teaching the Qur’an are presented in this study. The law governing the payment for teaching the Qur'an, as well as the legal procedures used by Hanafiyah Ulama and Syafiyah Ulama, are the source of the disagreement that leads to the issue. Normative legal research is the kind that it is. This study’s research topic relates to the views and legal strategies held by Syafiiyah and Hanafiyah scholars regarding compensation for Qur’an instruction. The research data are different viewpoints and justifications advanced by both traditional and modern academics. While the data sources are various fiqh references, such as books, papers, and newspapers, both print and electronic, which contain details about the status of receiving compensation for teaching the Qur’an services, as well as fiqh books written by classical and modern scholars regarding wages for doing so.The findings of the study on the opinions of the Ash-Shafi'i scholars suggest that charging for the teaching of the Qur’an is acceptable regardless of whether the pupils are children or adults, even when doing so would otherwise be considered fardhu 'ain. While the Hanafiyah scholars hold that it is forbidden to be paid for work that has religious overtones. argued that since Sahih hadiths were included in the quality of hadiths narrated by Bukhari, these hadiths should be used as support for claims that receiving or accepting compensation for teaching the Qur’an is acceptable.Keywords: Wages, Teacher, Perspective